Case Study: Harnessing Art Therapy for Patients With Learning Disability - Sanskriti Babhulkar; Caroline Deodhar (BJPsych Open)
Aims: Individuals with learning disabilities (LD) have a higher rate of mental health disorders and behavioural difficulties.